Nilai-Nilai Pendidikan Islam Pada Upacara Adat Kelahiran Suku Madura Di Kabupaten Kutai Kartanegara - Febriathie, Nur Aisyah; Khojir, Khojir; Kusasi, M. (Jurnal Tarbiyah dan Ilmu Keguruan Borneo, 2023)
Currently, innovation is developing from various sectors, including the education sector. In the world of education, innovations are often carried out when problems occur in the field related to education, so that solutions can be provided responsively. One of these problems is in terms of providing learning materials, where not a few school agencies change the methods and media used while still referring to educational goals and not contradicting government regulations. The objectives of conducting this research were 1) To explain the learning innovations of Islamic religious education, 2) to analyze innovations in methods and media for learning Islamic education. The design used in this study is a literature review. The data sources in this study were obtained from varous books and journals that have related topics with those the authors research in the form of innovative learning methods and learning media in Islamic religious education collected through Google Scholar with the articles used in the 2015-2022 publications. By using the keywords innovation of Islamic religious education learning methods and media. Based on the data collected, the results show that: (1) Learning methods and media will continue to innovate along with the times and technology, (2) Learning methods and media of various kids can be used according to the conditions or time of learning and the needs of the learning process.